The Development of Booklet about the Variety of Macroscopic Fungi Species in Arboretum Sylva Western Borneo as the Supplement of Learning Material at High School (Journal of Innovative Science Education, 2019)
This R & D research’s purposes are to calculate: a) the variety of microscopic fungi species used as booklet material development, b) the validity, readability, practice, and effectiveness of the booklet. The findings are: a) the 21 species of macroscopic fungi variety in Arboretum Sylva, consisting of two divisions namely Ascomycota and Basidiomycota, b) booklet validity based on material expert’s judgment, 93.5% and media expert, 98.8%, with valid criteria, c) 89.6% readability of the booklet by students and 91.2% by teacher, categorized as understandable, d) the practice of the booklet by the students, 87.5% and teachers, 86.9%, categorized as very practice, e) the effectiveness of the booklet based on affective learning achievement, 73.3 for experimental group, and 66.2 for control group with well category. Psychomotor learning achievement averages are 72.6 for experimental group and 61.1 for control group, categorized as well. Based on cognitive learning achievement, the gain scores are 0.71 for experimental group and 0.56 for control group. U Mann-Whitney test result gains significant score 0.000 < 0.05. Effective size calculation is 0.6 (categorized as medium) and has impacts as 38.2%. The conclusion is the use of booklet is effective toward students’ learning achievement.